The Effect of Multilingual Facilitation on Active Participation in MOOCs - Colas, Jean-François; Sloep, Peter B.; Garreta-Domingo, Muriel (International Review of Research in Open and Distributed Learning)

(untitled) (Athabasca University Press (AU Press), 2016)
A new approach for overcoming the language and culture barriers to participation in Massive Open Online Courses (MOOCs) is reported. It is hypothesised that the juxtaposition of English as the language of instruction, used for interacting with course materials, and one’s preferred language as the language of participation, used for interaction with peers and facilitators, is preferable to “English only” for participation in a MOOC. The Hands-On ICT (HANDSON) MOOC included seven teams of facilitators, each catering for a different language community. Facilitators were responsible for promoting active participation and peer tutoring. Comparing language groups revealed a series of predictors of intention to learn, some of which became apparent in the first days of the MOOC already. The comparison also uncovered four critical factors that influence participation: facilitation, language of participation, group size, and a pre-existing sense of community. Especially crucial was reaching a sufficient number of active participants during the first week. We conclude that multilingual facilitation activates participation in MOOCs in various ways, and that synergy between the four aforementioned factors is critical for the formation of the learning network that supports a social dynamic of active participation. Our approach suggests future targets for the development of the multilingual and community potential of MOOCs.